University Support Structures For Entrepreneurship In Algeria: The Scope And The Limits - Lounes Houda; Mancer Ilyes (جامعة الوادي University Of Eloued, 2024)
This study aims to examine support structures for entrepreneurship set up by university, what they have achieved and the obstacles encountered in carrying out theirmissions. These structures are: incubators, entrepreneurship centers and CATIs. We use an exploratory qualitative method;we collected data from the support structures through a survey sent to their directors; we received 39 responses from 79 questionnaires that were mailed, and 6 directors were interviewed.The study concludes that the performance of the structures in terms of projects supported or businesses created remains modest. Managers face number of difficulties: the absence of status for some structures, lack of autonomy and resources,and the weakness of networking. There is also the issue of recognition; managers' efforts are not rewarded. And, according to managers, entrepreneurial culture remains weak, which hinders the promotion of an entrepreneurial mindset.
Keywords: Incubation; Entrepreneurs; Start-up; University; Support for entrepreneurship